2021
DOI: 10.3390/ijerph18126370
|View full text |Cite
|
Sign up to set email alerts
|

Association of Mercury Exposure and Maternal Sociodemographics on Birth Outcomes of Indigenous and Tribal Women in Suriname

Abstract: Information regarding adverse birth outcomes (ABO) of Indigenous and Tribal women living in the remote tropical rainforest of Suriname, where mercury (Hg) use is abundant in artisanal gold mining, is not available. In the context of a health system analysis, we examined the association between Hg exposure, maternal sociodemographics on the ABO of Indigenous and Tribal women living in Suriname’s interior and its capital, Paramaribo. ABO were determined in pregnant women enrolled from December 2016 to July 2019 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 57 publications
1
2
0
Order By: Relevance
“…Comparing this study results with previous research, similar Hg levels were found with other communities in the Amazon region [ 30 , 31 , 36 , 38 , 39 , 40 , 41 ] and in South America [ 42 , 43 , 44 , 45 , 46 ], all exceeding internationally accepted safety levels for total Hg in hair [ 1 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Comparing this study results with previous research, similar Hg levels were found with other communities in the Amazon region [ 30 , 31 , 36 , 38 , 39 , 40 , 41 ] and in South America [ 42 , 43 , 44 , 45 , 46 ], all exceeding internationally accepted safety levels for total Hg in hair [ 1 ].…”
Section: Discussionsupporting
confidence: 89%
“…Alves et al [ 46 ] and Baldewsingh et al [ 47 ] found higher levels of Hg among rural than urban communities, as a result of less diverse diet patterns. Drouillet-Pinard et al [ 48 ] and Sakamoto et al [ 49 ] also found that hair Hg levels are mainly associated with fish consumption.…”
Section: Discussionmentioning
confidence: 99%
“…On the French side, 5% of children aged 6–11 years and 8% of those aged 12–16 years do not attend school ( 21 ). In Suriname, 79.6% of Amerindian women and 45.3% of Maroon women have no or primary education ( 22 ). Traditional lifestyle predominates and most households have no electricity, running water or sanitation.…”
Section: Introductionmentioning
confidence: 99%